Understanding government: four intellectual traditions in the study of public administration - Raadschelders, Jos C.N. (2008)
In this article a conceptual map of the identity of the study of public administration is developed that encompasses its theoretical diversity and richness. It organizes public administration scholarship into four main intellectual traditions: practical wisdom, practical experience, scientific knowledge and relativist perspectives. The objective is to outline the study's fundamental heterodoxy and interdisciplinariy. While the study clearly has strong national components everywhere, the four main intellectual traditions go across and beyond national traditions of government and of its study. - Reproduced.
Keywords: Public administration